Upaya Meningkatkan Rasa Percaya Diri Remaja Di Rumah Qur’an At-Taqwa - Bizarti, Iftitahun Ni’mah; Maghfirah, Nofia Puji; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
In adolescence, they begin to explore their identity, face pressure from the environment, and form views about themselves. One of the key aspects that is the foundation for the well-being and success of adolescents is self-confidence. Confidence is a belief in one's own abilities, self-esteem, and a positive perception of oneself. The purpose of this research is to find out the efforts made to foster self-confidence in adolescents at the At-Taqwa Qur'an House. The method used in this study is a qualitative method in which researchers describe and analyze efforts to increase adolescent self-confidence, with data collection techniques in the form of interviews and observations. Based on the results of the research that the researchers have done, the efforts made by young students in overcoming their lack of self-confidence are by changing negative mindsets to become positive, knowing their strengths and weaknesses and getting support from the closest people such as friends and family so they can build self-confidence positive for individuals.